Analisis Kompetensi Technology Pedagogy and Content Knowledge (TPACK) Guru SMP Plus Aisyah Samawa - Fahmi Yahya; Sri Nurul Walidain; Weni Wendari (Indonesian Publication Center, 2021)
This study aims to determine the TPACK ability of SMP Plus Aisyah Samawa teachers both in lesson planning and in learning implementation. The type of research used is descriptive research with survey method. The sampling technique used is purposive sampling, so the number of samples in this study were 33 people. The data collection technique in this study was through observation by taking all the necessary data. The data is in the form of lesson plans that have been made by the teacher and also observations of learning activities in the classroom, as well as testing the teacher's TPACK knowledge through tests. The results of the study concluded that the TPACK planning ability of SMP Plus Aisyah Samawa teachers was in accordance with the demands of the 2013 curriculum, but the implementation of TPACK was only limited to the use of focus and equipment along with whiteboards, and markers which were implemented in the process of teaching and learning activities with the presentation method in class by each student. each teacher. It means that the TPACK teacher’s ability of the SMP Plus Aisyah Samawa in planning and implementing learning is still lacking.